Vocational school teachers' readiness in implementing Curriculum 2013 revised edition in Cilacap Regency - Hanief Iqbal Saputra; Nuchron Nuchron (Jurnal Pendidikan Vokasi, 2019)
The purpose of this research is to reveal the factors that influence vocational school teachers' readiness to implement curriculum 2013 revised edition in Cilacap regency. The factors are 1) principals' leadership toward the teachers' readiness, 2) the impact of teachers' professionalism toward teachers' readiness, 3) the impact of the teachers' training. This research is an ex-post facto research. The method of collecting data used in this research is the mix method. The data was collected by using questioner and interview and then, analyzed by applying statistics descriptive counts mean of the percentage. To confirm the hypotheses, this study used multiple linear regression. The result of the research showed that: (1) principals' leadership affect teachers' readiness in the amount of 8.4%, (2) teachers' professionalism impact the teachers' readiness in amount of 17.7%, (3) teachers' training impact teachers' readiness in amount of 24.1%, and (4) principals' leadership, professionalism, and teachers' training simultaneously, affect teachers' readiness and it is proved by Fcalculate in the amount of 5,403 and significant value (p = 0,001 < 0,05). It meant that the whole result of the three free-variables affects the teachers' readiness significantly in implementing curriculum 2013 revised edition at vocational school in Cilacap.